2021
DOI: 10.46328/ijtes.266
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Tablet-Based Math Interventions: A Meta-Analysis

Abstract: There is debate over the effectiveness of using touch-screen tablet technology on overall student learning gains. This article provides a meta-analysis of studies that used tablets for the delivery of math interventions, programs, or apps to increase student math achievement. A total of 20 group design studies with 2,805 participants were included in the meta-analysis. Overall, tablet-based math interventions provided moderate positive effects for student math gains. Significant moderator variables included pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The influence of mobile learning on academic achievement has continued to grow rapidly in the last two decades, which has led to not only the increase of empirical studies (e.g., Cai et al, 2020;Thornton & Houser, 2005;Yeh et al, 2019;Zhang et al, 2020) but also the increase of systemic reviews and meta-analysis (e.g., Aspiranti & Larwin, 2021;Chen et al, 2021;Güzeller & Üstünel, 2016;Hassan Taj et al, 2016;Mahdi, 2018;Sung et al, 2015;Sung et al, 2017).…”
Section: Prior Meta-analysesmentioning
confidence: 99%
“…The influence of mobile learning on academic achievement has continued to grow rapidly in the last two decades, which has led to not only the increase of empirical studies (e.g., Cai et al, 2020;Thornton & Houser, 2005;Yeh et al, 2019;Zhang et al, 2020) but also the increase of systemic reviews and meta-analysis (e.g., Aspiranti & Larwin, 2021;Chen et al, 2021;Güzeller & Üstünel, 2016;Hassan Taj et al, 2016;Mahdi, 2018;Sung et al, 2015;Sung et al, 2017).…”
Section: Prior Meta-analysesmentioning
confidence: 99%
“…Lastly, several meta-analyses and systematic reviews have included math interventions across educational settings, for instance across kindergarten, elementary and middle school (i.e., K-12; Zhang and Xin, 2012;Lein et al, 2020;Ran et al, 2021;Dennis et al, 2022), across elementary and middle or high school (Templeton et al, 2008;Aspiranti and Larwin, 2021;Peltier et al, 2021), or across middle and high school (Jitendra et al, 2018;Zhang et al, 2022). In these reviews, larger effects were found for interventions conducted in the elementary grades than in higher grades, and for interventions developed and implemented by the researchers (Lein et al, 2020).…”
Section: Previous Reviews Of Math Intervention Studiesmentioning
confidence: 99%
“…As stated, Apple's App Store offers a myriad of education apps for all grade levels and subjects to run on the iPad. Thus, the iPad has justifiably gained increasing popularity as a mobile tablet for learning in the home and in the classroom (Aspiranti & Larwin, 2021;Hirsch-Pasek et al, 2015;Rideout, 2014Rideout, , 2017.…”
Section: The Educational Benefits Of Using Touchscreen Mobile Devicesmentioning
confidence: 99%
“…Leveraging knowledge from the Science of Learning, both theoretical and empirical research has attested that interactive, educational apps afford opportunities for engaging children in the repeated and varied practice of skills by integrating specific learning concepts into interactive gameplay and other activities (e.g., Aspiranti & Larwin, 2021;Griffith et al, 2020;Hirsh-Paseket al, 2015). For example, educational apps can be individualized to the child's pace and provide the child opportunities to engage in "drill and practice" as a means to independently master target skills and concepts (Hirsh-Pasek et al, 2015;Kim et al, 2021;Neumann et al, 2017;Papadakis et al, 2018).…”
Section: The Educational Benefits Of Using Touchscreen Mobile Devicesmentioning
confidence: 99%